EDUKASI DAN KOLABORASI UNTUK MASYARAKAT DENGAN HIPERTENSI PENERIMA VAKSIN 2 DI KOTA TANGERANG, BANTEN - Wijoyo, Eriyono Budi; Nainar, Azizah Al Ashri; Komariyah, Lilis; Nuraeni, Eni; Kartini, Kartini; Ismawati, Amalia (Universitas Muhammadiyah Tangerang, 2022)
The COVID-19 pandemic is still happening today. Many efforts have been made by the government to reduce the transmission of COVID-19, one of which is vaccination. The government has intensified the vaccination process. It is now being promoted for a second vaccination to the public at large. This service is carried out by a servant to the hypertension community who will carry out the second vaskin. A total of 14 people with hypertension were netted and education and collaboration were carried out to reduce hypertension. There were at least 12 people with hypertension who could continue the second vaccination and as many as 2 people could not continue the second vaccine. Education and collaboration carried out by the service staff are very effective in reducing blood pressure numbers in hypertension sufferers so that they can be given a second vaccine. There needs to be support from the wider community to get the widest possible vaccine so that vaccine achievements are also high and break the chain of spread of COVID-19.